Development and validation of the organizational nostalgia scale and its relationship with affective commitment and organizational discontinuity - Akgun, Ali E.; Tatar, Berivan; Erdil, Oya; Keskin, Halit; Muceldili, Busra (SPRINGER, 2023)
The concept of nostalgia has been investigated in various disciplines; however, conceptualization and operationalization of nostalgia at the organizational level remain nascent in the literature. Besides, there is a lack of empirical studies examining the role of organizational nostalgia on specific organizational behavior-related variables, such as affective commitment, with the contingent position of moderators, such as organizational discontinuity. To fill this gap, we performed four studies using a mixed methodology. In the first study, we conducted semi-structured interviews with 25 firms. We found that organizational nostalgia is a multidimensional construct with seven configural properties/dimensions: the organization's allegiance to employees, social events, management support, bonding between employees, the excitement of employees, work conditions, and physical work environment-related sentimental experiences/memories of the organization. In the second study, including 210 firms, and the third study involving 225 different firms, we tested the reliability and validity of the configural organizational nostalgia scale. Finally, in the fourth study, we tested the impacts of organizational nostalgia on affective commitment by investigating 101 other firms. Using a fuzzy-set qualitative comparative analysis (fsQCA), we found that the organization's allegiance to employees-related experiences/memories is a core condition of affective commitment. We also found that when there is less organizational discontinuity, the organization's allegiance to employees, management support, working conditions, and physical work environment-related experiences/memories are core conditions of affective commitment.
Keywords: Nostalgia; Organizational nostalgia; Affective commitment; Organizational discontinuity; Mixed-methods; NORMATIVE COMMITMENT; DEVELOPMENT-PROJECTS; WORK; VALIDITY; CULTURE; IDENTITY; LIFE; ANTECEDENTS; CONTINUANCE; RELIABILITY; Psychology